Isolation and Extraction of Medicinally Useful Dye from the Heartwood of Artocarpus integrifolia Linn. Using Different Solvents - Indrayan, A.K.; Shukla, R.K.; Kumar, Rajeev (Asian Journal of Chemistry, 2010)
Heartwood of Artocarpus integrifolia, an indigeneous tree, is a source of some medicianlly useful natural dyes which may vary in their shade and colour depending upon what solvent is used for extraction. They serve the dual purpose—colouring matter and treatment of certain ailments. Extraction in water, aqueous caustic soda, n-hexane yields respectively light chocolate solid (aqueous solution orange-red), dark reddish black-brown semi-solid (red-brown solution), light creamish greasy mass (colourless solution). In methanol as well as in ethanol a dark reddish brown semi-solid (red solution) is obtained while the NaOH extract on neutralisation yields a dark brownish black coloured solid; all expected to have varied medicinal value as well.